2019
DOI: 10.1080/03004430.2019.1590348
|View full text |Cite
|
Sign up to set email alerts
|

Influential factors on children's reading and writing development: the perspective of parents in a Swedish context

Abstract: Early reading and writing skills are important in order to develop and succeed, both in school and later on in life. The aim of this study was to shed light on influential factors on children's reading and writing development from the perspective of parents. Bronfenbrenner's bioecological model for human development was adopted as a theoretical framework. The researchers made use of retrospective lifehistory oriented interviews with 27 parents conducted as part of a larger research project in Sweden. In the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
9
0
5
Order By: Relevance
“…In other words, parents see helping their children learn to read as a natural responsibility (Epstein & Van Voorhis, 2012;Forsberg, 2007;Hoover-Dempsey, Bassler, & Burow, 1995) and may even derive pleasure from so doing (Levin et al, 1997). Such responses indicate that parents do not associate such support with educational equity, despite evidence that Swedish parents' backgrounds influence greatly children's reading competence (Axelsson, Lundqvist, & Sandberg, 2020;Myrberg & Rosén, 2009). The second, homework-negative, theme emerged from the utterances of four parents who spoke negatively about homework.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, parents see helping their children learn to read as a natural responsibility (Epstein & Van Voorhis, 2012;Forsberg, 2007;Hoover-Dempsey, Bassler, & Burow, 1995) and may even derive pleasure from so doing (Levin et al, 1997). Such responses indicate that parents do not associate such support with educational equity, despite evidence that Swedish parents' backgrounds influence greatly children's reading competence (Axelsson, Lundqvist, & Sandberg, 2020;Myrberg & Rosén, 2009). The second, homework-negative, theme emerged from the utterances of four parents who spoke negatively about homework.…”
Section: Discussionmentioning
confidence: 99%
“…Wang further discussed that in a growing number of studies it is revealed that older siblings can influence their younger siblings' language development directly or indirectly. Axelsson et al (2019) concurred that siblings can influence younger children's reading and writing development in terms of interest and motivation. In the interviews that were conducted parents mentioned how younger children would sit and watch whilst their older siblings did their homework.…”
Section: The Influence Of Siblingsmentioning
confidence: 99%
“…Bronfenbrenner explica que o desenvolvimento humano é uma progressiva acomodação entre o ser humano ativo e o seu entorno imediato, o que inclui dimensões conceptuais como pessoa, processo, contexto e tempo (Axelsson et al, 2019;Bronfenbrenner & Evans, 2000). Além disso, o processo de aprendizagem está influenciado pelas relações que se estabelecem entre: (i) os diferentes ambientes (meio envolvente), (ii) entre estes ambientes e os contextos, e (iii) entre os ambientes e os contextos de maior alcance, os quais chegam também a estar inclusos noutros ambientes e noutros contextos (Axelsson et al, 2019;Bronfenbrenner & Evans, 2000;Martins & Szymanski, 2004). É através destas premissas que Bronfenbrenner estabelece a ideia de um "ambiente ecológico."…”
Section: Teoria Da Ecologia E Do Desenvolvimento Humano De Bronfenbrennerunclassified
“…É através destas premissas que Bronfenbrenner estabelece a ideia de um "ambiente ecológico." Este ambiente deve ser entendido como um conjunto de estruturas seriadas, em que cada estrutura se estabelece por dentro da outra (Axelsson et al, 2019;Martins & Szymanski, 2004). Segundo esta ótica, poder-se-á potenciar o desenvolvimento da criança em estudo através duma intervenção, que deverá considerar os diferentes fatores que existem em diversos contextos e que se relacionam entre os seus diferentes meios envolventes (Figura 1).…”
Section: Teoria Da Ecologia E Do Desenvolvimento Humano De Bronfenbrennerunclassified
See 1 more Smart Citation